A produção de sentido na arte contemporânea: texto curatorial em uma perspectiva multiculturalista - Schütz, Danielle (My University, 2019)
The purpose of this dissertation is to evaluate the role of the curator in relation to his / her social context. With the premise that art expresses the vanguard, it takes as its object three curatorial texts of events of great national repercussion in recent years: the Queermuseu (Porto Alegre and Rio de Janeiro editions) and the Mercosul Biennial, in 2018, in order to verify , through the analysis of the content of these texts, if the curatorship is in tune with contemporary guidelines, in a multiculturalist perspective. The research course includes references on history and art education, especially in Brazil, as well as the role of the curator and the evolution of his / her performance. Boaventura Santos, Mbembe, Archer and Bourriaud are part of the multidisciplinary theoretical axis.
A presente dissertação tem o objetivo de avaliar o papel do curador em relação ao seu contexto social. Tendo como premissa que a arte expressa a vanguarda, toma como objeto três textos curatoriais de eventos de grande repercussão nacional nos últimos anos: a Queermuseu (edições Porto Alegre e Rio de Janeiro) e a Bienal do Mercosul, de 2018, a fim de verificar, por meio da análise de conteúdo desses textos, se a curadoria está sintonizada com as pautas contemporâneas, em uma perspectiva multiculturalista. O percurso de pesquisa contempla referências sobre história e ensino da arte, especialmente no Brasil, bem como o papel do curador e a evolução de sua atuação. Boaventura Santos, Mbembe, Archer e Bourriaud integram o eixo teórico multidisciplinar.
Keywords: Curadoria; Museus - Curadoria; Multiculturalismo; Arte moderna - Séc. XX; Curatorship; Museum - Curatorship; Multiculturalism; Art, Modern - Séc. XX